Number of strictures predictive of recurrent surgical intervention in a paediatric population with obstructive crohn's disease. (13th March 2011) - Bamford, R; Hay, A; Kumar, D
Abstract : Introduction: 70–90% of Crohn's patients will require surgery with younger patients often requiring further procedures. Our aim was to investigate whether the number of strictures at the time of surgery can be used to predict the need for further surgical intervention. Methods: Patients under 20 years of age undergoing surgery between 1 January 2000 and 1 June 2009 were identified. Data was collected on procedures for stenotic Crohn's disease, including previous surgery outside the original inclusion dates. Therefore operations between 12 December 1996 and 16 February 2009 are represented. Patients were divided into two groups; group 1 with less than 4 strictures and group 2 with 4 or more strictures. Recurrence was defined as the need for further surgical intervention and Kaplan Meir method was used to analyse the data. Results: 26 patients and 40 operations were identified. Mean age was 15.57 years (7.2–19.4) with equal numbers of males and females. 19 operations were strictureplasties, 13 were resections and 8 were combined procedures. Mean follow-up was 67.44 months (10.5–156.6). 20/40 (50%) procedures involved the terminal ileum, 9/40 (22.5%) the ileo-colic junction, 8/40 (20%) the upper GI tract and 3/40 (7.5%) the colon. Group 1 consisted of 29/40 (72.5%) procedures and group 2 11/40 (27.5%). Recurrence rate for all operations was 35% (14/40). Patients in group 1 had significantly less recurrence than group 2 (24% vs 63.6%, p=0.033). Conclusion: Children and adolescents with 4 or more strictures at the time of surgery are likely to require further surgical intervention and should be counselled and managed as such.